A Computerised Tomographic assessment of structural changes in the human brain with aging (International Journal of Biomedical Research, 2014)
Background : Computerised Tomography (CT) scan of brain is a useful tool to detect structural changes in the brain with accuracy and safety. Aging is associated with gradual loss of normal brain tissue that can cause greater levels of decline in cognition and leads to low quality of life. This decline is found to occur only after a particular age. Material and Methods : The study was conducted on 98 healthy subjects belonging to both sexes between the age of 20 85 years. CT scan was performed to assess the size of the ventricles of the brain and cortical sulci. Results : Data was analysed using appropriate software to know the significance of the change with aging. The cerebral ventricles were found to enlarge along with thinning of the cortical sulci which was found to be significant (p 0.05). Discussion: The enlargement is not uniform throughout the ventricular system and is found to be relatively early and significantly more in the frontal brain regions which has a more complex structure with late maturation.